Mapping the grassland quality of the flooded plain based on Jilin-01 images with a red-edge spectral band - Chen, Ziqi; Zhang, Yanhong; Zang, Peng; Liu, Zhaoli; Zhao, Wenbin (Frontiers in Earth Science, 2023)
In response to the difficulties of flood plain quality assessment, red-edge spectral remote sensing data acquired from the Jilin-01 satellite were used. The Grassland Quality Index (GQI) was formed by the Normalized Difference Vegetation Index (NDVI) and Normalized Difference Red Edge Index (NDRE) related to the determination of grassland quality and the first principal component of the red-edge Chlorophyll Index obtained by principal component analysis. The GQI was applied to evaluate grassland quality in the flooded plain, which is an important grassland ecological-barrier area in the western area of Jilin Province, and was then verified using field measurement data. Results show that 1) 80% of grasslands in Xianghai Nature Reserve are of a medium quality, and the grasslands with good growth status account for approximately 15% and are mainly concentrated in the wetland and swamp areas in the central south part of the reserve and that 2) the correlation of the evaluation results was verified using the survey field biomass, and the coefficient of the empirical correlation model is 0.96, which indicates good consistency. This study is of practical significance for the timely and accurate monitoring of grassland growth, which is beneficial for the development of livestock husbandry and the protection of the ecological environment in northern China.